Islamic Approach towards Import and Export: A Research Analysis in the Context of Umar’s (RA) Vision - Khan, Irfan Ullah; Kaleem Ullah, (Journal of Islamic and Religious Studies, 2020)
International trade relations are a branch of economics that deals with trade between countries. It covers exports and imports of goods and services. Besides, international treaties and their International institutions are also analyzed. Also, the measure of the development of any country is that there should be high imports and exports. In various respects, a large part of the foreign exchange that we collect throughout the year is spent on importing various goods from other countries. That is why our economy cannot grow as fast as it should. One of the reasons why our foreign exchange reserves have not increased significantly is the gap between imports and exports. As far as the United States, the United Kingdom, and Europe are concerned, we have a trade deficit with many countries in the region because we order more and export less. In this way, bilateral trade is beneficial for them, but not for us. As the field of international economic relations is getting wider and wider day by day and its importance is increasing, the more the country develops, the more it evolves. The level of international economic relations at that time was not as high as they were in the time of Hazrat Omar. The trade reserves did not pass close to the status of the exchange. But the knowledge of international economic relations on Islamic Minhaj. In terms of age, Hazrat Omar's economic knowledge and insight were much higher than the people of that time. The rules and regulations that you have laid down for him. At every age, every country and every person strives to gain benefits and gains through international economic relations and to avoid difficulties and losses. So, in this article, the light of the thoughts and insights of the Islamic Minhaj Hazrat Umar RA on international trade will be presenting a research review.